The Relationship Between Hb Levels of Pregnant Women and the Incidence of Low-birth-weight (LBW) Babies at the Bere-Bere Community Health Center - Eka Sukma; Raden Maria Veronika Widiatrilupi (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Anemia during pregnancy is a significant health issue that contributes to the incidence of low-birth-weight (LBW) babies. At the Bere-Bere Community Health Center, the prevalence of LBW is 15%, higher than the national average, and the prevalence of anemia in pregnant women is 30%. This study aimed to analyze the relationship between hemoglobin (Hb) levels in pregnant women and the incidence of LBW at the center. A cross-sectional design was used with 30 pregnant women selected via purposive sampling. Hb levels were categorized into anemia (Hb <11 g/dL) and normal (Hb ≥11 g/dL), while birth weight was categorized into LBW (<2500 grams) and normal (≥2500 grams). Data analysis was performed using univariate and bivariate analysis with the Chi-Square test. Results showed that 43.3% of pregnant women experienced anemia and 33.3% of babies had LBW. Of the 13 anemic mothers, 61.5% gave birth to LBW babies, while only 11.8% of mothers with normal Hb levels had LBW babies. The Chi-Square test revealed a significant relationship (p = 0.004, p < 0.05) between maternal Hb levels and LBW incidence. In conclusion, maternal anemia is significantly associated with LBW, highlighting the need for interventions such as iron supplementation, nutrition education, and regular check-ups to prevent anemia and reduce LBW rates.